Dysregulation in erythrocyte dynamics caused by SARS-CoV-2 infection: possible role in shuffling the homeostatic puzzle during COVID-19 - Michelle Mendanha Mendonça; Kellen Rosa da Cruz; Denise da Silva Pinheiro; Gean Carlos Alves Moraes; Patricia Maria Ferreira; Marcos Luiz Ferreira-Neto; Eduardo Sérgio da Silva; Reggiani Vilela Gonçalves; Gustavo Rodrigues Pedrino; James O. Fajemiroye; Carlos Henrique Xavier (Hematology, Transfusion and Cell Therapy, 2022)
Introduction: The evolving COVID-19 pandemic became a hallmark in human history, not only by changing lifestyles, but also by enriching scientific knowledge on viral infection and its consequences. Objective: Although the management of cardiorespiratory changes is pivotal to a favorable prognosis during severe clinical findings, dysregulation of other systems caused by SARS-CoV-2 infection may imbalance erythrocyte dynamics, such as a bidirectional positive feedback loop pathophysiology. Method and Results: Recent evidence shows that SARS-CoV-2 is capable of affecting the genetics and dynamics of erythrocytes and this coexists with a non-homeostatic function of cardiovascular, respiratory and renal systems during COVID-19. In hypothesis, SARS-CoV-2-induced systematical alterations of erythrocytes dynamics would constitute a setpoint for COVID-19-related multiple organ failure syndrome and death. Conclusion: The present review covers the most frequent erythrocyte-related non-homeostatic findings during COVID-19 capable of providing mechanistic clues of SARS-CoV-2-induced infection and inspiring therapeutic-oriented scientific evidence.